EVALUATION EXECUTION TIME FEATURES OF SIMPATI WEB-BASED MONITORING AND EVALUATION APPLICATION USING AUTOMATION TESTING - Arifin, Nur; Agustin, Ninik; Anggoro, Tri (Informatika, Universitas Jenderal Soedirman, 2024)
One of the data collection methods employed in monitoring and evaluation is a survey. The advantages of information technology-based surveys include a reduced risk of data loss and the ability to access the survey system from any location. Consequently, it is imperative to devise a web-based monitoring and evaluation system. In this study, the monitoring and evaluation system was developed using an Agile methodology and implementing automation testing. The Agile development method was utilized to create this application through the stages of design, development, testing, deployment, and feedback. The system was developed using the PHP programming language and the MySQL database. Automation testing was conducted using Katalon Studio. The design and implementation of the web-based SIMPATI application resulted in a system capable of monitoring and evaluating higher education with main features such as multi-user support, online surveys, a real-time database, and data visualization. Automation testing using Katalon Studio demonstrated that all features in the system run well and are stable. However, there is a discrepancy in the execution time for each test case. This discrepancy is attributed to the intricacy of the test cases and external factors such as system load, server performance, and network conditions. The fastest execution time for the login feature is 11 seconds, while the longest execution time for the add new user feature is 4 minutes and 29 seconds. In conclusion, automation testing in web-based system development employing agile methods can assist in the rapid and repeatable evaluation of system performance.